Pendidikan Kristen Responsif Disrupsi: Integrasi Nilai Kristiani Dalam Transformasi Pendidikan Abad Ke-21 - Boiliu, Esti Regina; Kia, A. Dan (Pusat Riset dan Inovasi Nasional, 2025)
Christian education faces significant challenges in the era of digital disruption, where technology and social changes require rapid adaptation in curricula and teaching methods. This research aims to explore how Christian values can be integrated into the digital curriculum in Christian schools, the readiness of teachers in developing faith-based pedagogies, and the potential of digital strategies to instill Christian values in Generation Alpha. The research uses a qualitative approach with a literature review, examining related literature on Christian education, transformative pedagogy, and theories of digital generations and digital literacy. The novelty of this research lies in its focus on combining Christian value integration with the rapidly developing digital education technologies and its contribution to character formation in the digital generation. The research findings indicate that the integration of Christian values into the digital curriculum should be approached holistically and contextually, utilizing technology to deepen moral and spiritual teachings. Furthermore, the readiness of Christian teachers to implement transformative faith-based pedagogies is essential for ensuring authentic character formation. The potential of digital strategies to educate Generation Alpha, as digital natives, can be maximized through interactive and innovative media. In conclusion, Christian education in the era of disruption requires a balance between technology and faith, where technology is used as a tool to introduce and reinforce Christian values in the lives of young people.